Author Correction: Behaviour reactions of bottlenose dolphins (Tursiops truncatus) to multirotor Unmanned Aerial Vehicles (UAVs) - Ticiana Fettermann (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.